Skip to content Skip to sidebar Skip to footer

May-Jun-21-p1-CIE-0606/11 : Solution





2021 (May-June) CIE (0606-Additional Mathematics), Paper 1 ၏ Question နှင့် Solution များ ဖြစ်ပါသည်။ Question Paper ကို ဒီနေရာမှာ Download ယူနိုင်ပါသည်။











  1. (a) On the axes, sketch the graph of $y = 5(x+1)(3x-2)(x-2)$, stating the intercepts
    with the coordinate axes.



    [3]




    (b) Hence find the values of x for which $5(x+1)(3x-2)(x-2)>0$ .



    [2]


  2. SOLUTION
    (a) $y=5(x+1)(3 x-2)(x-2)\\\\ $


    When $y=0$,


    $\begin{aligned}
    &\\
    &5(x+1)(3 x-2)(x-2)=0 \\\\
    &\therefore\ x=-1 \text { or } x=\dfrac{2}{3} \text { or } x=2\\\\
    \end{aligned}$


    $\therefore$ The graph cuts $x$-axis at $(-1,0),\left(\dfrac{2}{3}, 0\right)$ and $(2,0)$.



    When $x=0, y=20\\\\ $.


    The graph cuts $y$ axis at $(0,20)$.




    (b) The set of the values of $x$ to satisfy the inequality $5(x+1)(3 x-2)(x-2)>0$ is
    $\left\{x \mid-1<x<\dfrac{2}{3} \text { or } x>2\right\}. $






  3. Find $\displaystyle\int_{3}^{5}\left(\dfrac{1}{x-1}-\dfrac{1}{(x-1)^{2}}\right) \mathrm{d} x$,
    giving your answer in the form $a+\ln b$, where $a$ and $b$ are rational numbers.



    [5]





  4. SOLUTION
    $\begin{aligned}
    \text { let } u&=x-1 \\\\
    \therefore\ d u&=d x \\\\
    \text { When } x&=3, u=2 \\\\
    \text { When } x&=5, u=4\\\\
    \end{aligned}$


    $\begin{aligned}
    & \int_{3}^{5}\left(\frac{1}{x-1}-\frac{1}{(x-1)^{2}}\right) d x \\\\
    =& \int_{2}^{4}\left(\frac{1}{u}-\frac{1}{u^{2}}\right) d u \\\\
    =& \int_{2}^{4} \frac{1}{u} d u-\int_{2}^{4} \frac{1}{u^{2}} d u \\\\
    =& \int_{2}^{4} \frac{1}{u} d u-\int_{2}^{4} u^{-2} d u \\\\
    =&\left.\ln u\right]_{2}^{4}+\left.\frac{1}{u}\right]_{2}^{4} \\\\
    =&(\ln 4-\ln 2)+\frac{1}{4}-\frac{1}{2} \\\\
    =& \ln \frac{4}{2}-\frac{1}{4} \\\\
    =&-\frac{1}{4}+\ln 2
    \end{aligned}$



  5. The polynomial $p(x)=a x^{3}-9 x^{2}+b x-6$, where $a$ and $b$ are constants,
    has a factor of $x-2 .$ The polynomial has a remainder of $66$ when divided by $x-3$.



    (a) Find the value of $a$ and of $b$.



    [4]





    (b) Using your values of $a$ and $b$, show that $p(x)=(x-2)q(x)$ , where $q(x)$ is
    a quadratic factor to be found.



    [2]





    (c) Hence show that the equation $p(x) = 0$ has only one real solution.



    [2]


  6. SOLUTION
    $\begin{aligned}
    \text{(a) } \quad &p(x)=a x^{3}-9 x^{2}+b x-6 \\\\
    & x-2 \text { is a factor of } p(x) . \\\\
    \therefore\ & p(2)=0 \\\\
    & 8 a-3 b+2 b-6=0 \\\\
    & 4 a+b=21 \ldots(1)\\\\
    \end{aligned}$



    $\quad $ When $p(x)$ is divided by $(x-3)$,


    $\begin{aligned}
    &\\
    \quad\ \text{ the remainder } &=p(3)\\\\
    \therefore\ p(3)&=66\\\\
    27 a-81+3 b-6 &=66 \\\\
    9 a+b &=51 \ldots(2)\\\\
    \end{aligned}$


    Solving equation $(1)$ and $(2)$,


    $\begin{aligned}
    &\\
    \quad &a=6 \text { and } b=-3 \\\\
    &\therefore p(x)=6 x^{3}-9 x^{2}-3 x-6\\\\
    \end{aligned}$


    $\text{(b) } \quad\ $ Let $6 x^{3}-9 x^{2}-3 x-6=(x-2)\left(6 x^{2}+k x+3\right)$.


    $\begin{aligned}
    &\\
    \quad\ \therefore\ 6 x^{3}-9 x^{2}-3 x-6 &=6 x^{3}-12 x^{2}+k x^{2}-2 k x+3 x-6 \\\\
    &=6 x^{3}+(k-12) x^{2}+(3-2 k) x-6 \\\\
    \therefore\ k-12 &=-9 \\\\
    \therefore\ k &=3 \\\\
    \therefore\ 6 x^{3}-9 x^{2}-8 x-6 &=(x-2)\left(6 x^{2}+3 x+3\right)\\\\
    \therefore\ q(x) &=6 x^{2}+3 x+3 \\\\
    \end{aligned}$


    $\begin{aligned}
    \text{(c) } \quad\ \text { When } 6 x^{3}-9 x^{2}-8 x-6 &=0 \\\\
    (x-2)\left(6 x^{2}+3 x+3\right) &=0 \\\\
    6(x-2)\left(x^{2}+\dfrac{1}{2} x+\dfrac{1}{2}\right) &=0 \\\\
    (x-2)\left(x^{2}+\dfrac{1}{2} x+\dfrac{1}{16}+\dfrac{7}{16}\right) &=0 \\\\
    (x-2)\left(\left(x+\dfrac{1}{4}\right)^{2}+\dfrac{7}{16}\right) &=0 \\\\
    \text{Since } \left(x+\dfrac{1}{4}\right)^{2}+\dfrac{7}{16} &>0, \\\\
    x-2 &=0 \\\\
    \therefore\ x &=2\\\\
    \end{aligned}$


    $\therefore$ There is only one real solution for $p(x)=0$.



  7. The first 3 terms in the expansion of $(a+x)^{3}\left(1-\dfrac{x}{3}\right)^{5}$,
    in ascending powers of $x$, can be written in the form $27+b x+c x^{2}$, where $a, b$
    and $c$ are integers. Find the values of $a, b$ and $c$.

    [8]





  8. SOLUTION
    $\begin{aligned}
    (a+x)^{3}\left(1-\frac{x}{3}\right)^{5} &=27+b x+c x^{2}+\cdots \\\\
    \left(a^{3}+3 a^{2} x+3 a x^{2}+x^{3}\right)\left(1-5\left(\frac{x}{3}\right)+10\left(\frac{x}{3}\right)^{2}+\cdots\right) &=27+b x+c x^{2}+\cdots \\\\
    \left(a^{3}+3 a^{2} x+3 a x^{2}+x^{3}\right)\left(1-\frac{5 x}{3}+\frac{10 x^{2}}{9}+\cdots\right) &=27+b x+c x^{2}+\cdots \\\\
    \left(a^{3}-\frac{5 a^{3}}{3} x+\frac{10 a^{3}}{9} x^{2}+3 a^{2} x-5 a^{2} x^{2}+3 a x^{2}+\cdots\right) &=27+b x+c x^{2}+\cdots \\\\
    a^{3}+\left(3 a^{2}-\frac{5 a^{3}}{3}\right) x+\left(\frac{10 a^{3}}{9}-5 a^{2}+3 a\right) x^{2}+\cdots &=27+b x+c x^{2}+\cdots\\\\
    \end{aligned}$


    $\begin{aligned}
    \quad\therefore\quad a^{3} &=27 \\\\
    a &=3\\\\
    b &=3 a^{2}-\frac{5 a^{3}}{3} \\\\
    &=3\left(3^{2}\right)-\frac{5(27)}{3} \\\\
    &=27-45 \\\\
    &=-18 \\\\
    c &=\frac{10 a^{3}}{9}-5 a^{2}+3 a \\\\
    &=\frac{10(27)}{9}-5(3)^{2}+3(3) \\\\
    &=30-45+9 \\\\
    &=-6
    \end{aligned}$



  9. The functions $f$ and $g$ are defined as follows.

    $\begin{aligned}
    &\\
    &f(x)=x^{2}+4 x \text { for } x \in \mathbb{R} \\\\
    & g(x)=1+e^{2 x} \text { for } x \in \mathbb{R}\\\\
    \end{aligned}$



    (a) Find the range of $f$.



    [2]




    (b) Write down the range of $g$.


    [1]




    (c) Find the exact solution of the equation $fg(x) = 21$,
    giving your answer as a single logarithm.


    [4]


  10. SOLUTION
    $\begin{aligned}
    \text{(a) } \hspace{1.5cm} f(x) &=x^{2}+4 x, x \in R \\\\
    f(x) &=x^{2}+4 x+4-4 \\\\
    f(x) &=(x+2)^{2}-4 \\\\
    (x+2)^{2} & \geq 0 \text { for all } x \in \mathbb{R} \\\\
    (x+2)^{2}-4 & \ge-4 \\\\
    \therefore \quad f(x) & \ge-4\\\\
    \text{(b) }\hspace{1.5cm} g(x)&=1+e^{2 x}, x \in \mathbb{R}\\\\
    \end{aligned}$


    $\qquad$ Since $e^{2 x}>0$ for all $x \in \mathbb{R}$,


    $\begin{aligned}
    &\\
    1+e^{2 x} &>1 \\\\
    \therefore\ g(x) &>1\\\\
    \text{(c) }\hspace{2cm} f g(x)&=21\\\\
    f(g(x)) &=21 \\\\
    f\left(1+e^{2 x}\right) &=21 \\\\
    \left(1+e^{2 x}+2\right)^{2}-4 &=21 \\\\
    \left(e^{2 x}+3\right)^{2} &=25 \\\\
    e^{2 x}+3 &=5 \\\\
    e^{2 x} &=2 \\\\
    2 x &=\ln 2 \\\\
    x &=\frac{1}{2} \ln 2 \\\\
    &=\ln \sqrt{2}
    \end{aligned}$






  11. (a) (i) Find how many different 5-digit numbers can be formed using the digits
    1, 3, 5, 6, 8 and 9. No digit may be used more than once in any 5-digit number.



    [1]




    (ii) How many of these 5-digit numbers are odd?



    [1]




    (iii) How many of these 5-digit numbers are odd and greater than 60000?



    [3]




    (b) Given that $45 \times{ }^{n} \mathrm{C}_{4}=(n+1) \times{ }^{n+1} \mathrm{C}_{5}$,
    find the value of $n$.


    [4]


  12. SOLUTION
    $\begin{aligned}
    \text{(a) (i) } \quad & { }^{6} P_{5}=720\\\\
    \quad\text{(ii) }\quad & \text{Total number of 5-digit odd numbers} \\\\
    =&\ 4 \times 5 ! \\\\
    =&\ 480\\\\
    \text{(iii) } \quad &\text{Total number of 5-digit odd numbers start with 6 and 8}\\\\
    =&\ 2 \times 4 \times 3 \times 2 \\\\
    =&\ 192\\\\
    &\text{Total number of 5 -digit odd numbers start with 9 }\\\\
    =&\ \times 4 \times 3 \times 3 \\\\
    =&\ 72\\\\
    \therefore\ &\text{Total number of 5-digit odd numbers } > 6000\\\\
    =&\ 192+72 \\\\
    =&\ 264\\\\
    \end{aligned}$


    $\begin{aligned}
    \text{(c) } \hspace{1.5cm} 45 \times{ }^{n} C_{4} &=(n+1) \times{ }^{n+1} C_{5} \\\\
    45 \times \frac{n !}{4 !(n-4) !}&=(n+1) \times \frac{(n+1) !}{5 !(n+1-5) !}\\\\
    4 !(n-4) ! &=(n+1) \times \frac{(n+1) n !}{5 \times 4 !(n-4) !} \\\\
    45 &=\frac{(n+1)^{2}}{5} \\\\
    (n+1)^{2} &=225\\\\
    n+1 &=15 \\\\
    n &=14
    \end{aligned}$







  13. (a) In this question, all lengths are in metres and time, t, is in seconds.





    The diagram shows the displacement–time graph for a runner, for $0\le t\le 40$.



    (i) Find the distance the runner has travelled when $t = 40$.





    [1]




    (ii) On the axes, draw the corresponding velocity–time graph for the runner, for $0\le t\le 40$.





    [2]







    (b) A particle, $P$, moves in a straight line such that its displacement from
    a fixed point at time $t$ is $s$. The acceleration of $P$ is given by
    $(2 t+4)^{-\frac{1}{2}}$, for $t>0$.





    (i) Given that $P$ has a velocity of $9$ when $t=6$, find the velocity of $P$ at time $t$.




    [3]






    (ii) Given that $s=\dfrac{1}{3}$ when $t=6$, find the displacement of $P$ at time $t$.



    [3]


  14. SOLUTION
    (i) At $0 \leq t <10$


    distance travelled by runner $=50 \mathrm{~m}$


    At $10 \leq t<40$,


    distance travelled by runner $=60 \mathrm{~m}$


    the distance the runner has travelled when $t=40$ is


    $(50+60)=110 \mathrm{~m}$



    (ii) $0 \leqslant t<10$,


    $\quad v=\dfrac{50}{10}=5 \mathrm{~m} / \mathrm{s}$


    $\quad 10 \leq t \leq 40$,


    $\quad v=\dfrac{-10-50}{40-10}=\dfrac{-60}{30}=-2 \mathrm{~m} / \mathrm{s}$






    $\begin{aligned}
    \text { (b) } \quad \text { displacement } &=s\\\\
    \text { velocity } &=\frac{d s}{d t} \\\\
    \text { acceleration } &=\frac{d^{2} s}{d t^{2}} \\\\
    \frac{d^{2} s}{d t} &=(2 t+4)^{-1 / 2}, t>0 \\\\
    \text { velocity } &=\displaystyle\int(2 t+4)^{-1 / 2} d t\\\\
    \text { Let } u &=2 t+4 \\\\
    d u &=2 d t \\\\
    d t &=\frac{1}{2} d u \\\\
    \text { velocity } &=\frac{1}{2} \int u^{-1 / 2} d u \\\\
    &=\sqrt{u}+c_{1} \\\\ &=\sqrt{2 t+4}+c_{1} \\\\
    \text { When } t &=6, v=9 . \\\\
    9 &=\sqrt{16}+c_{1} \\\\
    c_{1} &=5 \\\\
    \therefore\ \frac{d s}{d t} &=\sqrt{2 t+4}+5 \text { (at time t) } \\\\
    \text { displacement } &=\int(\sqrt{2 t+4}+5) d t \\\\
    &=\int \sqrt{2 t+4} d t+5 \int d t \\\\
    &=\frac{1}{2}(2 t+4)^{3 / 2}+5 t+c_{2}\\\\
    s &=\frac{1}{3} \text { When } t=6 \\\\
    \frac{1}{3} &=\frac{1}{3}(12+4)^{3 / 2}+5(6)+c_{2} \\\\
    \frac{1}{3} &=\frac{1}{3}(64)+30+c_{2} \\\\
    \therefore\ c_{2} &=-51 \\\\
    \therefore\ s &=\frac{1}{3}(2 t+4)^{3 / 2}+5 t-51
    \end{aligned}$



  15. DO NOT USE A CALCULATOR IN THIS QUESTION.



    A curve has equation $y=(2-\sqrt{3}) x^{2}+x-1$. The $x$-coordinate of a point $A$
    on the curve is $\dfrac{\sqrt{3}+1}{2-\sqrt{3}}$.



    (a) Show that the coordinates of $A$ can be written in the form $(p+q \sqrt{3}, r+s \sqrt{3})$,
    where $p, q, r$ and $s$ are integers.



    [5]




    (b) Find the $x$-coordinate of the stationary point on the curve, giving your answer
    in the form $a+b \sqrt{3}$, where $a$ and $b$ are rational numbers.



    [3]


  16. SOLUTION
    $\begin{aligned}
    \text{ (a) } \quad \text{ Curve } : y&=(2-\sqrt{3}) x^{2}+x-1\\\\
    \frac{\sqrt{3}+1}{2-\sqrt{3}} &=\frac{\sqrt{3}+1}{2-\sqrt{3}} \times \frac{2+\sqrt{3}}{2+\sqrt{3}} \\\\
    &=\frac{2 \sqrt{3}+3+2+\sqrt{3}}{4-3} \\\\
    &=5+3 \sqrt{3}\\\\
    \text{ When } x&=5+3 \sqrt{3},\\\\
    y &=(2-\sqrt{3})(5+3 \sqrt{3})^{2}+5+3 \sqrt{3}-1 \\\\
    &=(2-\sqrt{3})(25+30 \sqrt{3}+27)+4+3 \sqrt{3}\\\\
    y &=(2-\sqrt{3})(52+30 \sqrt{3})+4+3 \sqrt{3} \\\\
    y &=104-52 \sqrt{3}+60 \sqrt{3}-90+4+3 \sqrt{3} \\\\
    &=18+11 \sqrt{3}\\\\
    \end{aligned}$


    $\qquad \therefore$ The coordinates of the point $A$ is
    $(5+3 \sqrt{3}, 18+11 \sqrt{3}).$



    $\begin{aligned}
    &\\
    \text{ (b) } \quad \frac{d y}{d x}&=2(2-\sqrt{3}) x+1
    \end{aligned}\\\\ $


    $\qquad$ At stationary point,


    $\begin{aligned}
    &\\
    \frac{d y}{d x} &=0 . \\\\
    \qquad 2(2-\sqrt{3}) x+1 &=0 \\\\
    x &=\frac{1}{2 \sqrt{3}-4}\\\\
    x &=\frac{1}{2 \sqrt{3}-4} \times \frac{2 \sqrt{3}+4}{2 \sqrt{3}+4} \\\\
    &=\frac{2 \sqrt{3}+4}{12-16} \\\\
    &=\frac{2 \sqrt{3}+4}{-4} \\\\
    &=-1-\frac{\sqrt{3}}{2}\\\\
    \end{aligned}$








  17. (a) (i) Write $6 x y+3 y+4 x+2$ in the form $(a x+b)(c y+d)$, where $a, b, c$ and $d$
    are positive integers.



    [1]





    (ii) Hence solve the equation $6 \sin \theta \cos \theta+3 \cos \theta+4 \sin \theta+2=0$
    for $0^{\circ} <\theta<360^{\circ}$.




    [4]





    (b) Solve the equation $\dfrac{1}{2} \sec \left(2 \phi+\dfrac{\pi}{4}\right)=\dfrac{1}{\sqrt{3}}$
    for $-\pi<\phi<\pi$, where $\phi$ is in radians. Give your answers in terms of $\pi$.




    [5]




  18. SOLUTION
    $\begin{aligned}
    \text { (a) (i) }\quad & 6 x y+3 y+4 x+2 \\\\
    =& 3 y(2 x+1)+2(2 x+1) \\\\
    =&(2 x+1)(3 y+2)\\\\
    \end{aligned}$


    $\begin{aligned}
    \quad\text{ (ii) } \quad 6 \sin \theta \cos \theta+3 \cos \theta+4 \sin \theta+2&=0\\\\
    \therefore(2 \sin \theta+1)(8 \cos \theta+2) &=0 \\\\
    \sin \theta=-\frac{1}{2} \text { or } \cos \theta &=-\frac{2}{3}\\\\
    \end{aligned}$


    $\begin{aligned}
    \qquad\text { For } \sin \theta &=-\frac{1}{2} \\\\
    \theta &=210^{\circ} \text { or } \\\\
    \theta &=330^{\circ} \\\\
    \text { For } \cos \theta &=-\frac{2}{3} \\\\
    \theta &=180-48.2 \text { or } \\\\
    \theta &=180^{\circ}+48.2^{\circ} \\\\
    \therefore \theta &=131.8^{\circ} \text { or } \\\\
    \theta &=228.2^{\circ}\\\\
    \end{aligned}$


    $\begin{aligned}
    \text { (a) (i) } &\quad \frac{1}{2} \sec \left(2 \phi+\frac{\pi}{4}\right)=\frac{1}{\sqrt{3}},-\pi<\phi<\pi \\\\
    &\sec \left(2 \phi+\frac{\pi}{4}\right)=\frac{2}{\sqrt{3}} \\\\
    &\cos \left(2 \phi+\frac{\pi}{4}\right)=\frac{\sqrt{3}}{2}\\\\
    \end{aligned}$


    $\qquad \therefore$ basic acute angle (reference angle) $=\dfrac{\pi}{6}$


    $\begin{aligned}
    &\\
    \qquad \cos \left(2 \phi+\frac{\pi}{4}\right)&>0 \\\\
    \end{aligned}$


    $\qquad \therefore 2 \phi+\dfrac{\pi}{4}$ lies either
    in the $1^{\text {st }}$ or $4^{\text {th }}$
    quadrant.


    $\begin{aligned}
    &\\
    \qquad 2 \phi+\frac{\pi}{4} &=\frac{\pi}{6} \text { or } \\\\
    2 \phi+\frac{\pi}{4}&=-\frac{\pi}{6} \text { or }\\\\
    2 \phi+\frac{\pi}{4}&=\frac{13 \pi}{6} \text { or }\\\\
    2 \phi+\frac{\pi}{4}&=\frac{11 \pi}{6} \\\\
    \qquad \therefore \phi &=-\frac{\pi}{24} \text { or }\\\\
    \phi&=-\frac{5 \pi}{24} \text { or } \\\\
    \phi&=\frac{23 \pi}{24} \text { or } \\\\
    \phi&=\frac{19 \pi}{24}
    \end{aligned}$



  19. In this question all lengths are in centimetres.




    The diagram shows a shaded shape. The arc $AB$ is the major arc of a circle, centre $O$, radius $10$.
    The line $AB$ is of length $15$, the line $OC$ is of length $25$ and the lengths of $AC$ and $BC$ are
    equal.




    (a) Show that the angle $AOB$ is $1.70$ radians correct to $2$ decimal places.



    [2]




    (b) Find the perimeter of the shaded shape.




    [4]





    (c) Find the area of the shaded shape.





    [5]




  20. SOLUTION
    $\begin{aligned}
    &\\
    \qquad \cos (\angle A O B) &=\frac{10^{2}+10^{2}-15^{2}}{2(10)(10)} \\\\
    &=-\frac{1}{8} \\\\
    \angle A O B &=1.70 \text{ rad}\\\\
    \end{aligned}$


    $\begin{aligned}
    \text{ (b) } \quad &\text{ The perpendicular distance from } O \text{ to } A B\\\\
    &=\sqrt{10^{2}-\left(\frac{15}{2}\right)^{2}} \\\\
    &=6.61\\\\
    \therefore\ & \text{ The perpendicular distance from } C \text{ to } A B\\\\
    &=25-6.61 \\\\
    &=18.39\\\\
    \end{aligned}$


    $\begin{aligned}
    & A C=B C=\sqrt{18.32^{2}+7.5^{2}} \\\\
    &=19.86 \\\\
    &\quad \text { length of major sector }\\\\
    &=(2 \pi-1.7) \times 10 \\\\
    &=45.83 \\\\
    \therefore & \text { perimeter of shadld region } \\\\
    =&\ 2(19.8 b)+45.83 \\\\
    =&\ 85.55\\\\
    \end{aligned}$


    $\begin{aligned}
    &\quad \text{ area of major sector }\\\\
    &=\frac{1}{2} \times 10^{2}(2 \pi-1.7) \\\\
    &=229.15 \\\\
    &\quad \text { area of kite AOBC } \\\\
    &= \frac{1}{2} \times 25 \times 15 \\\\
    &=187.5 \\\\
    &=229.15+187.55 \\\\
    &=416.65
    \end{aligned}$

Post a Comment for "May-Jun-21-p1-CIE-0606/11 : Solution"

Sponsored by: iklanvideo.io